Aphakia Correction by Injection of Foldable Intra Ocular Lens in the Anterior Chamber. (January 2013) - Giles, Kagmeni; Ernest, Moukouri; Christelle, Domngang; Georges, Nguefack-Tsague; Raoul, Cheuteu; Come, Ebana Mvogo; Wiedemann, Peter
We assessed the outcomes of the use of anterior chamber foldable lens for unilateral aphakia correction at the University Teaching Hospital of Yaounde. In this retrospective, non-comparative, consecutive case series study, we reviewed the records of patients who underwent an operation for aphakia correction by the means of injection of an angular supported foldable lens between January 2009 and December 2011 in the University Teaching Hospital Yaounde. Student's paired t -test was carried out to compare preoperative and postoperative visual acuity (VA) and intraocular pressure (TOP). P -values less than 0.05 were considered statistically significant. Twenty-one patients were included in the study; twelve were male (57.1%) and nine were female (42.9%). The mean age was 55.38 ± 17.67 years (range 9–75 years). The mean follow-up duration was 5.95 ± 3.14 months (range 2–12 months). The mean logMAR visual acuity was 1.26 ± 0.46 pre-operatively and 0.78 ± 0.57 post-operatively ( P = 0.003). The change in intraocular pressure was not statistically significant. Complications included intraocular hypertension (over 21 mmHg) in 3 patients (14.3%) and macular edema, pupillar ovalization, and retinal detachment in one patient each. The results indicate that injection of an angular support foldable lens in the anterior chamber is a useful technique for the correction of aphakia in eyes without capsular support. More extended follow-up, however, and a larger series of patients are needed to ascertain the effectiveness and safety of this procedure.